Evolution and Optimization of Tooth Models for Testing In Vivo EPR Tooth Dosimetry - Kobayashi, Kyo (Radiat Prot Dosimetry, 2016)
Testing and verification are an integral part of any cycle to design, manufacture and improve a novel device intended for use in humans. In the case of testing Dartmouth's electron paramagnetic resonance (EPR) in vivo tooth dosimetry device, in vitro studies are needed throughout its development to test its performance, i.e. to verify its current capability for assessing dose in individuals potentially exposed to ionizing radiation. Since the EPR device uses the enamel of human teeth to assess dose, models that include human teeth have been an integral mechanism to carry out in vitro studies during development and testing its ability to meet performance standards for its ultimate intended in vivo use. As the instrument improves over time, new demands for in vitro studies change as well. This paper describes the tooth models used to perform in vitro studies and their evolution to meet the changing demands for testing in vivo EPR tooth dosimetry.